Reverse integration in wheelchair basketball: stakeholders` understanding in elite and recreational sporting communities - Verdonck, M.; Ripat, J.; Clark, P.; Oprescu, F.; Gray, M.; Chaffey, L.; Kean, B. (Adapted Physical Activity Quarterly, 2023)
Wheelchair basketball (WCBB) often includes reverse integration (RI), defined as the inclusion of athletes without impairment in a sport traditionally aimed at athletes with an impairment. This study explored how RI in WCBB was understood by internal stakeholders. Data were gathered from athletes, coaches, and administrators at an Australian club competition and at a Canadian elite training center. Analysis of semistructured interviews with 29 participants led to the identification of eight themes. Collectively, the findings showed that RI was embedded within WCBB, RI was considered to be a way to advance the growth and improve the quality of WCBB as well as a way to increase awareness of WCBB and disability. There were some concerns that RI may not be equitable, as WCBB is a "disability sport." Stakeholders` perspectives on RI could provide useful information for sport policymakers, managers, administrators, sports organizations, and athletes interested in further developing WCBB.